An example of a Bayes factor false positive finding for clinical research - Cristian Antony Ramos Vera (Revista Cubana de Medicina Militar)
A false positive finding of a significant result reported in this journal was reported, by contrasting the Bayesian reanalysis, which estimated a greater probability of the null hypothesis compared to the alternate correlation hypothesis.